Kelembagaan Penari Keraton Yogyakarta Masa Sultan Hamengku Buwana V - Supriyanto Supriyanto (Institut Seni Indonesia Surakarta, 2010)
In the Yogyakarta palace, during the reign of Sultan Hamengku Buwana V (1823-1855), there was an interesting phenomenon surrounding the classification of Wayang Wong (a form of traditional Javanese dance drama) dancers as human actors who replaced the role of puppets. The naming of such groups, who were referred to as classes of dancers, was like the certification of different social levels, according to their race, within the administrative laws governing foreigners in the Sultanate. The first class was known as Ringgit Gupermen, the group to which the best dancers belonged. The second class was given the name Ringgit Encik and consisted of the middle level dancers. The final class was Ringgit Cina which was for the beginners. The existence of such characteristics meant that the awareness of the different classes of Wayang Wong dancers during the reign of Hamengku Buwana V had multiple tendencies. On the one hand, the existence of such classes was a bureaucratic framework with political tendencies; while on the other hand, class was an artistic framework with cultural tendencies. In the pursuit of political tendencies, classes of dancers formed a structural balance, which in turn created a balance in civilization. Keywords : Ringgit GupermenÂ